2018
DOI: 10.1186/s12875-018-0868-5
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning conversations with palliative patients: looking through the GP’s eyes

Abstract: BackgroundAlthough it is often recommended that general practitioners (GPs) initiate advance care planning (ACP), little is known about their experiences with ACP. This study aimed to identify GP experiences when conducting ACP conversations with palliative patients, and what factors influence these experiences.MethodsDutch GPs (N = 17) who had participated in a training on timely ACP were interviewed. Data from these interviews were analysed using direct content analysis.ResultsFour themes were identified: AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(91 citation statements)
references
References 44 publications
2
83
0
6
Order By: Relevance
“…A previous study showed the importance of a valid explanation of the concept of PC beforehand [39], since without confronting patients with PC beforehand, they might still associate PC with oncoming death only [44]. However, there are of course patients who could benefit from PC, but cannot accept it, even after sufficient clarification [48].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed the importance of a valid explanation of the concept of PC beforehand [39], since without confronting patients with PC beforehand, they might still associate PC with oncoming death only [44]. However, there are of course patients who could benefit from PC, but cannot accept it, even after sufficient clarification [48].…”
Section: Discussionmentioning
confidence: 99%
“…In ES, for example, palliative care in hospitals has improved considerably over the course of this study, possibly leading to an increase in end-of-life conversations taking place in the hospital instead of the primary care setting 14. In the NL, a recent study showed that GPs were more hesitant to engage in ACP with patients who were still being treated by specialists in hospital, as these patients are often less open to discussion 33. Numerous initiatives have been developed to make earlier integration of specialised palliative care services a reality 34–37.…”
Section: Discussionmentioning
confidence: 99%
“…When and whether identification occurs seems to be highly dependent on a patient's diagnosis [18]. Whereas prognostication and the weighting of treatment options is a clear transition point to the palliative phase in cancer patients, in non-cancer patients, prognostication is considered more difficult which was also found within the primary care setting [16,17,32,33]. In patients with organ failure, so-called 'prognostic paralysis' can occur, where, because of the uncertainty in prognosis, physicians do not tell patients they have reached the end stage of their disease and do not plan appropriate care [34,35].…”
Section: Main Findings and Comparison With Other Studiesmentioning
confidence: 99%
“…However, only a few physicians in our study described consulting with patients' GPs. GPs themselves experience this lack of collaboration as an important barrier to improving care for patients at the end of life [33,43].…”
Section: Main Findings and Comparison With Other Studiesmentioning
confidence: 99%